Sacubitril/Valsartan as a Therapeutic Tool Across the Range of Heart Failure Phenotypes and Ejection Fraction Spectrum - Gallo, Giovanna; Volpe, Massimo; Battistoni, Allegra; Russo, Domitilla; Tocci, Giuliano; Musumeci, Maria Beatrice (Frontiers in Physiology, 2021)
Heart failure (HF) is a complex syndrome caused by a variety of structural or functional cardiac abnormalities as a consequence of several involved pathophysiological pathways. In the last decades, left ventricular ejection fraction (LVEF) has represented the principal criterion used to stratify HF, to interpret ventricular function and to identify therapeutic strategies. However, this chimeric parameter oversimplifies the multiple pathways and mechanisms underlying the progression of HF. Indeed, HF should be more appropriately considered as the final stage of multiple disease states, characterized by distinct phenotypes on the basis of key clinical and molecular variables, such as underlying etiologies and conditions, demographic and structural features and specific biomarkers. Accordingly, HF should be viewed as a continuous spectrum in which the specific phenotypes need to be accurately identified with the aim to improve the disease management with a more tailored approach. In such a complex and heterogeneous scenario, the clinical benefits of an angiotensin receptor neprilysin inhibition strategy, namely in the single pill sacubitril/valsartan (S/V), have been shown across the entire HF continuum, representing a fundamental therapeutic strategy, although with different magnitudes depending on the severity and the stage of the clinical syndrome. In this viewpoint paper we have reconsidered the role of S/V in the light of different HF phenotypes and on the basis of HF considered as a whole spectrum.